Effects of understory fire management treatments on California Hazelnut, an ecocultural resource of the Karuk and Yurok Indians in the Pacific Northwest - Marks-Block, Tony; Lake, Frank K.; Curran, Lisa M. (Forest ecology and management, 2019)
•Karuk and Yurok Indians rely on fire to enhance ecocultural resources.•Fire and proxy treatments increase densities of California hazelnut basketry stems.•Modified fuel reduction treatments support ecocultural resource production.•Field experiment integrates Indigenous and Western science approaches. Before widespread fire exclusion policies, American Indians used broadcast understory fires or cultural burns to enhance resources integral for their livelihood and cultural practices. To restore ecocultural resources depleted from decades of fire exclusion and to reduce wildfire risks, the Karuk and the Yurok Tribes of Northwest California are leading regional collaborative efforts to expand broadcast fires and fuel reduction treatments on public, private, and Tribal lands in their ancestral territories. Through collaboration with Karuk and Yurok Tribal members and basketweavers, we evaluated the effects of broadcast fires and three fire proxy treatments on California hazelnut shrubs (Corylus cornuta var. californica) that produce highly valued ecocultural resources for basketry materials. Across a 10 ha Douglas-fir and mixed hardwood forest (500 m a.s.l.) in the Klamath mountains, we established 27 stratified blocks (16 m2) and within each block applied three fire proxy treatments designed and used by Tribal members with an untreated control. These treatments involved manual hazelnut stem cutting, directly blistering hazelnut stems via propane torch, and igniting surface fuels piled within hazelnut shrubs to top-kill stems. Broadcast fire was applied to 12 separate blocks. After a full growing season (12–18 months post-treatment/burn), shrubs were re-measured. We then harvested these stems (n = 604; 50 shrubs) across treatments and compared results with stems gathered independently by two experienced Karuk/Yurok basketweavers (n = 396 and n = 73) from an adjacent broadcast burned site. Compared to the untreated shrubs, pile burning, propane torching, and broadcast burning increased basketry stem production by 7–10 fold (p < 0.001), while the cutting treatment increased production by 4-fold (p = 0.006). Shrubs with relatively greater access to sunlight (southern aspect, ≥51% and <70% canopy cover) produced fewer quality stems when compared to shrubs with an eastern aspect (p < 0.01) and ≥70% canopy cover (p < 0.05). Harvested stems across all treatments displayed similar stem length distributions to those gathered by one of the two basketweavers (p > 0.05). Our results demonstrate that these fire-proxy methods are an effective means to increase the production and quality of basketry materials. Expanding the area and frequency of targeted understory fire-based forest treatments on private, public and Tribal lands in California and the Pacific Northwest would substantially increase the availability of these fire-enhanced ecocultural resources that are currently limited in supply and in high demand.